EDUCATION OF THE CULTURE OF COMMUNICATION OF PRIMARY SCHOOL STUDENTS IN THE EXTENDED DAY GROUP IN SCHOOLS OF THE MOUNTAIN REGION - Kilichenko, Oksana (Mountain School of Ukrainian Carpaty, 2020)
The article considers the peculiarities of the formation and development of the culture of communication of children of primary school age in the different age group of the extended day. The essence of the concept of "culture of communication" is analyzed and defined. It is determined that primary school is the beginning of the most important process for the socialization of the individual age period, as it contributes to the formation of an extended day group as a contact group where children learn new norms, values, stereotypes of behavior. The influence of the organization of the beginning on the level of group relations, the content of the social experience of each individual is noticed. It is noted that the primary school age is the most socially significant and the most pedagogically insidious period, because deviations in the formation of personality are often masked by a protective form of behavior (diligence, obedience). However, the primary school age is unique in the presence of experience of free communication. It becomes the basis of cultural norms, which are tested later in a variety of communication situations. It is a sensitive period in the formation of a culture of communication, as it is characterized by the following features: instinct, trust, pliability, the need for emotional contact with peers, the tendency to imitate. All this contributes to the development of skills to intelligently analyze, recognize and evaluate one`s actions and deeds, to seek and find ways to achieve the goal, to be able to overcome obstacles and difficulties. The different age of an extended day group is heterogeneous in its social situation and psychological characteristics. Therefore, there are two periods: adaptation (6-9 years) and pre-adolescent (9-10 years). The study of the process of forming a culture of communication was organized in a different age group of an extended day in a primary school in a mountain environment. As our observations of students in extended day group and conversation with educators show, a characteristic feature of junior students' communication is their close communication with adults, which takes place in the learning process, at school (during the lessons and extended day group) and at home; informing adults about their affairs and the affairs of the class; asking adults for information on specific issues (we often call them “Chomuchki”). In elementary school, girls are more likely to initiate communication. The main directions of formation of the culture of communication in the group of the extended day are defined: development of culture of verbal and nonverbal communication, struggle against profanity, development of ability of attentive listening.